Effectiveness of the Entomopathogenic Fungal Species Metarhizium anisopliae Strain NCAIM 362 Treatments against Soil Inhabiting Melolontha melolontha Larvae in Sweet Potato (Ipomoea batatas L.) - Putnoky-Csicsó, Barna (J Fungi (Basel), 2020)
The effect of fungal entomopathogen M. anisopliae strain NCAIM 362 against M. melolontha larvae in sweet potato was tested under open field conditions when crop management included compost supply and soil cover (agro-foil or agro-textile). Additionally, the effect of M. anisopliae same strain against M. melolontha was compared with the effect of α-cypermethrin under greenhouse conditions. Soil microbial community using Illumina sequencing and soil biological activity were tested as possible parameter influencing M. anisopliae effect. According to the results, compost supply and textile cover may enhance the effectiveness of M. anisopliae under open field conditions, while no effect of fungal treatment was detected under greenhouse conditions. Even if soil parameters (chemical composition, bacterial, and biological activity) were identical, the effect of α-cypermethrin against M. melolontha larvae was significant: lower ratio of larval survival and less damaged tubers were detected after the chemical treatment. Our results suggest that M. anisopliae strain NCAIM 362 is not effective to control M. melolontha larvae, further pieces of research are needed to test other species of the Metarhizium genus to find an effective agent for sustainable pest control in sweet potato.